Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 22415 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Lithobates catesbeianus (Shaw, 1802)", { "or" : [ "Country is Canada", "Country is United States of America", "Country is Mexico" ] }, "BasisOfRecord is Specimen" ] } The dataset includes 22415 records from 83 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000456-170627171947987/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences